P223 Efficacy and safety of tacrolimus in Crohn's disease: a nationwide, multi-centric study from GETECCU. (25th January 2019) - Rodriguez-Lago, I; Castro-Poceiro, J; Fernández-Clotet, A; Mesonero, F; López-Sanromán, A; López-García, A; Márquez, L; Clos-Parals, A; Cañete, F; Vicuña, M; Nantes, Ó; Merino, O; et al.
Abstract: Background: Crohn's disease (CD) is chronic inflammatory disease of the gastrointestinal tract. Tacrolimus (TCR) is a calcineurin inhibitor drug commonly used for prophylaxis of rejection in renal and liver transplantation. There is some evidence on the short- and medium-term efficacy and safety of TCR in CD, but data are still scarce. The primary aim of our study was to evaluate the efficacy and safety of TCR in CD in clinical practice in Spain. Methods: We performed a retrospective, multi-centric study in 22 inflammatory bowel disease Units in Spain. We included all adult patients with an established diagnosis of CD in whom oral TCR was prescribed for this condition. Clinical response was assessed by Harvey–Bradshaw index (H-B) and physician global assessment after 3 months. Perianal disease was evaluated by fistula drainage assessment (FDA) at the same time point. Follow-up period was considered until the last visit during therapy or 12 months after stopping the drug. Descriptive statistics and non-parametric tests were used in the statistical analysis. Results: Between January 2000 and November 2017 a total of 85 patients received TCR (mean age 36 years; 55% female; 69% perianal disease; mean CRP 14 mg/l). The most common indications for TCR were refractory luminal disease (57%) and perianal disease (32%). Most patients (81%) had previously received at least one anti-TNF agent and 61% ≥2. Blood drug levels were 5–10 ng/ml during induction (34%) and maintenance (47%). In 25% of cases, TCR was started concomitantly with systemic steroids, in 11% with an anti-TNF agent and in 6% with vedolizumab. The drug was maintained for a median time of 6 months (2.7–18) and the median follow–up was 28 months (15–56). We found statistically significant differences in H-B after 3 months (median 7.4 (SD 4.4), p = 0.014). FDA showed a complete response in 8%, while 34% had partial response. In the univariate analysis, concomitant thiopurines were significantly associated with short-term clinical response (OR 5.53 95% CI 1.36–22.5, p = 0.017). We observed statistically significant differences in CRP levels 1, 3, 6, and 12 months when compared with baseline ( p < 0.03). The drug was stopped in 86% of patients after a median time of 6 months (2–17): 62% requiring a new immunomodulator, 44% hospitalisation and 42% surgery. A total of 34% patients suffered adverse events related to the drug (45% tremor, 28% acute kidney injury), and in 37% they led to the discontinuation of the drug. Conclusions: Tacrolimus shows a clinical benefit in CD in the short-term, but its lower long-term effectiveness and frequent adverse events remain relevant issues in clinical practice.